Penilaian Kualitas Instrumen Media Pengajaran Portal E-Modul Materi Sistem Peredaran Darah - Radeswandri Radeswandri; Anggie Dwimaya Amanda; Rian Vebrianto (Universitas Muhammadiyah Surabaya, 2023)
Utilization of good media can be used as an optimization of students in carrying out the learning process. The E-module of the Circulatory System is one of the transformation media resulting from technological developments that can attract students' attention and interest in reading. In this study, to produce the E-module of the Circulatory System as a quality media, it is necessary to evaluate 3 constructs, namely product design, information contained, and product effectiveness. Data collection techniques were carried out by filling out online questionnaires with data processing analysis using SPSS version 23. The results of testing the validity of the Corrected Item – Total Correlation value were above 0,3; and reliable as evidenced by the coefficient on Cronbach's alpha > 0,6, which is 0,69. The results of the analysis show that the instruments used meet the valid and reliable criteria. Therefore, the Circulatory System E-module can be used for learning.